PENERAPAN BALANCED SCORECARD SEBAGAI TOLAK UKUR KINERJA (STUDI EMPIRIS PADA KOPERASI WANITA â€œBAKTI PERTIWIâ€) - GITA AFARA, LAILA (Jurnal Akuntansi AKUNESA, 2017)
This study aims to analyze performance of Koperasi Wanita "Bakti Pertiwi" (Kopwan) using Balanced Scorecard, in order to expand its business unit. The performance assessments consists of financial perspective, customer perspective, internal business processes perspective, and learning and growth perspective. Using survey method on 50 respondents consists of customers, members and employees of Kopwan; this study finds that the performance of financial perspective is fluctuated, all financial performance measures show significant declining in 2013. The finding for customer perspective shows that on average satisfaction of members was very satisfied and liveliness level is 59.18%. The performance of internal business processes perspective is not good because still limited to one business unit. In addition, average employee satisfaction of Kopwan’s products shows highly satisfied; the last finding is among administrators and members of Kopwan have good relationships. Keywords: Balanced Scorecard, Performance, Women Cooperative